(untitled) (International Journal of Engineering and Computer Science, 2017)
OFDM is a bandwidth efficient multicarrier modulation where the available spectrum is divided into subcarriers, with each subcarrier containing a low rate data stream. OFDM has gained a tremendous interest in recent years because of its robustness in the presence of severe multipath channel conditions with simple equalization, robustness against Inter-symbol Interference (ISI), multipath fading, in addition to its high spectral efficiency. However, the Peak-to-Average Power Ratio (PAPR) is a major drawback of multicarrier transmission system such as OFDM. High PAPR increases the complexity of analog-to-digital (A/D) and digital-to-analog (D/A) converters, and lowers the efficiency of power amplifiers. The aim of this project work is to investigate the OFDM scheme, and realize a fully functional system in software and analyzing how it reduces the Peak to Average Power Ratio (PAPR). Different PAPR Reduction techniques developed for OFDM are analyzed, based on the Computational Complexity, Bandwidth expansion and error performance. In this Project work, new Companding Transform Techniques is developed for PAPR reduction of OFDM system. This guarantees the improved performance in terms of BER while reducing PAPR effectively and efficiently.